The marvel of social market economy: Things we do not talk about - Iulian Oneașcă (European Institute of Romania, 2024)
The paper promotes the performance of the European market as a measure of the efficiency of its societies. The social market economy and the international standards of the social sciences and disciplines are essential to providing prosperity for all. The economic perspective comes naturally. A multi-methodological approach is employed. It involves a modified and generalized theory of social systems, heuristics, and casuistry. The general objective is translated into specific objectives that condition its approach: reassessing the understanding of the single market, outlining an adequate framework for promoting societal efficiency, and some positive, normative, and policy contributions. The research highlights the nurtured limits of the single market, introduces the social market economy and its constructed barriers, analyses its specifics, and presents things that are not talked about. It finishes by discussing, concluding, and making relevant recommendations, attempting to provide realworld advice to scientists and policymakers.
Keywords: D70; K10; O10; 330; social market economy; economy of effort; change; European Union